Preparation, Electronic Properties, and Powder-XRD Structure Analysis of 3,5-Bis(pyridin-2-yl)-H-1,2,4-triazoledichloridocopper(II) - Kristian Handoyo Sugiyarto; Isti Yunita; Harold Andrew Goodwin (Indonesian Journal of Chemistry, 2020)
Salt of [Cu(bptrzH)Cl2], (bptrzH = 3,5-bis(pyridin-2-yl)-H-1,2,4-triazole) has been prepared and characterized its electronic spectral and magnetic properties. This salt is paramagnetic with magnetic moment, μs, being 1.77–1.78 BM at 293 K, but decreased significantly with decreasing temperature to be 0.60–0.63 BM at 90 K, indicating antiferromagnetic nature. This is associated with Cu–Cu magnetic interactions at low temperatures, and suggests that the salt adopt an octahedrally polymeric structure. The electronic spectrum of this salt reveals a strong ligand field band centered at about 13,000 cm–1 and a very strong charge transfer absorption at about 23,000–24,000 cm–1. The spectrum is better resolved at lower temperature and this is parallel to the slight change in color from yellowish-green at room temperature to bright green at low temperature (90 K). The powder XRD of this complex was refined by Le Bail method of Rietica program and found to be fit as triclinic symmetry of space group PĪ with the figure of merit: Rp = 5.02; Rwp = 7.95; Rexp = 5.40; Bragg R-Factor = 0.05; and GOF = 2.166.